2019
DOI: 10.1108/ijrdm-09-2018-0204
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of sensory experience: engagement vs diversive exploration

Abstract: Purpose The purpose of this paper is to examine the dual effect of sensory experiences on customer behaviour in the context of retailing. Based on the theoretical framework of the optimal stimulation level theory, the authors propose that sensory experiences reinforce satisfaction, engagement and loyalty, but increase customers’ diversive exploration and curiosity for other experiences and may eventually led to reduced loyalty. Design/methodology/approach A self-administrated online questionnaire was distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…Furthermore, the results suggest that travelers with a high propensity to seek variety are more demanding than those with a low variety seeking level. Individuals with a high variety seeking look for new experiences or stimuli to meet their OSL level; but, according to Lashkova et al (2019), sensory experiences associated with hedonic products (atmospherics and environment of the hotel, in this case) involve learning that generates higher consumer expectations, making consumers more demanding and leading them to seek new sensations. This is consistent with the results found by Lai and Hitchcock (2017), which show that the attributes that provided satisfaction to the guests varied depending on the frequency of accommodation (new, repeat and frequent travelers).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the results suggest that travelers with a high propensity to seek variety are more demanding than those with a low variety seeking level. Individuals with a high variety seeking look for new experiences or stimuli to meet their OSL level; but, according to Lashkova et al (2019), sensory experiences associated with hedonic products (atmospherics and environment of the hotel, in this case) involve learning that generates higher consumer expectations, making consumers more demanding and leading them to seek new sensations. This is consistent with the results found by Lai and Hitchcock (2017), which show that the attributes that provided satisfaction to the guests varied depending on the frequency of accommodation (new, repeat and frequent travelers).…”
Section: Discussionmentioning
confidence: 99%
“…The propensity to seek variety also relates to sensation seeking, that is, the search for varied, novel and complex experiences or sensations and the desire to face risks in favor of Website quality and star rating signals on booking intention such experiences (Olsen et al, 2016). In the retail sector, Lashkova et al (2019) show that sensory experiences involve learning that generates new and higher consumer expectations, making consumers more demanding and leading them to explore or seek new sensations and alternatives.…”
Section: Moderating Role Of Travelers' Variety Seekingmentioning
confidence: 99%
“…Philosophy and psychology literature studies (e.g. Connell and Lynott, 2016; Lashkova et al. , 2019) have identified human senses as an instrument for gathering information about the external world and for exploration (Lashkova et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Philosophy and psychology literature studies (e.g. Connell and Lynott, 2016;Lashkova et al, 2019) have identified human senses as an instrument for gathering information about the external world and for exploration (Lashkova et al, 2019). With the advent of the phenomenon of experiential marketing (Schmitt, 1999) and service experience (Hightower et al, 2002), the emphasis was laid on stimulating the customers' senses, feelings, thoughts and actions and relate the same to a company and its brands.…”
Section: Sensory Experiencementioning
confidence: 99%
“…A sensory experience is an important determinant of customers' brand experience and a pleasant sensory experience enhances customer satisfaction, engagement and loyalty (Lashkova et al, 2020). In this study, we attempted to uncover the role of visual aesthetics of food items in online menus and the mechanism by which visual aesthetics engage consumers in multisensory experiences and influence purchase intention when they use online food delivery services through a mobile app.…”
Section: Introductionmentioning
confidence: 99%